PEMBUATAN SUMUR RESAPAN AIR HUJAN DAN LUBANG RESAPAN BIOPORI DI DESA SUKOHARJO, PRINGSEWU - Nurul Mawaddah; Resarizki Utami; Mutiara Fajar; Nabila Putriyandri Alifa; Fajriharish Nur Awan (Jurnal Pengabdian Pendidikan Masyarakat (JPPM), 2023)
At the end of 2022, precisely in October-November 2022, Pringsewu Regency experienced the worst flood disaster in the last 12 years. As many as three pekon (villages) in Pringsewu Regency, Lampung, were flooded after being showered with heavy rain overnight. One of the villages affected by the floods is the Sukoharjo Village. As a result, for rice fields that have poor drainage channels, rainwater creates new problems, especially for rice farmers. too much water inundated crops. Socialization and demonstrations can be used to increase the knowledge of a group of respondents. Socialization and demonstrations regarding making infiltration wells and biopori infiltration holes have been carried out to provide information and knowledge to respondents regarding groundwater conservation issues, to get to know rainwater infiltration wells and biopori infiltration holes to reduce floods and landslides during the rainy season and as raw water reserves for activities people during the dry season. The method of implementing this service is a pre-test and post-test in the form of filling out questionnaires to respondents, namely residents. The results of the activity showed an increase in the percentage of residents' knowledge which increased from 64.29% to 86.43%.